Jose Maceda / Ading (1978) a critical dialogue - Baes, Jonas (Musika Jornal, 2014)
In the last few years leading to his untimely demise in May 2004, Jose Maceda had continued to work on new musical pieces, while finding every opportunity to discuss his ideas especially with his closest colleagues. While theories of musical systems in Asia and his notions of a new musical renaissance were the recurrent themes of these discussions, this opened the opportunity for Jonas Baes to dialogue with him about his work along the lines of the author's growing interest in social theory, in relation to the realities of Philippine society, then already plunged into the global political economy and the neo-feudal world order. This paper "crystallizes" those last dialogues with Maceda, giving focus on what Baes refers to as the apotheosis of his creative work: Ading (1978).